First person - Kaitly Woodard (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Kaitly Woodard is first author on ' Limitations of mouse models for sickle cell disease conferred by their human globin transgene configurations', published in DMM. Kaitly conducted the research described in this article while a graduate student in Mitchell J. Weiss's lab at St. Jude Children's Research Hospital, Memphis, TN, USA. She is now a Senior Scientist II in the lab of Mir Hossain at Novartis Institutes for BioMedical Research, Cambridge, MA, USA, investigating gene therapy for haemoglobinopathies.